Multi-omics data integration in anorexia nervosa patients before and after weight regain: A microbiome-metabolomics investigation. Issue 3 (March 2021) - Monteleone, Alessio Maria; Troisi, Jacopo; Fasano, Alessio; Dalle Grave, Riccardo; Marciello, Francesca; Serena, Gloria; Calugi, Simona; Scala, Giovanni; Corrivetti, Giulio; Cascino, Giammarco; Monteleone, Palmiero; Maj, Mario
Summary: Background & aims: We have recently reported specific fecal metabolomic changes in acute and short-term weight restored patients with anorexia nervosa (AN). In this study we explored the association between those metabolomic changes and patients' gut microbiome composition. Methods: The gut microbiome of AN women was sequenced in both the underweight phase (n = 21) and after short-term weight restoration (n = 16) and compared to that of 20 healthy women. According to a multi-omics approach, microbiome data were correlated with 49 relevant fecal metabolites previously characterized in our participants by an untargeted metabolomic procedure. Results: Compared to healthy women, AN patients showed a decreased intra-individual bacterial richness, an increased Bacteroidetes-to-Firmicutes abundance ratio and significant changes in the relative abundances of several bacteria at phylum, class, order, family and genus levels. These changes were observed in both the underweight and weight-restored condition. Moreover, the relationships among the 49 previously selected fecal metabolites and bacteria genera showed structures of different complexity among the 3 groups. In particular, a quarter of those relationships showed a divergent direction in the acutely ill patients with respect to the weight-restored ones or normal controls. Finally, in acutely ill patients 70% of those correlations showed a negative sign suggesting a prevalent metabolites consummation by gut microbiome. Conclusions: These data confirm a profound perturbation in the gut microbiome composition of AN patients. Moreover, for the first time, they provide the evidence that in AN gut bacteria are connected with several fecal metabolites in a different way from normal controls and with divergent directions in the acute phase with respect to the weight-restored phase. Highlights: The gut microbiota regulates host appetite, body weight and brain functions. It has been proposed to have a role in the pathophysiology of anorexia nervosa (AN). Gut microbiota dysbiosis was found in acutely ill and weight-restored patients with AN. In AN gut bacteria genera were associated to relevant fecal metabolites in a specific way.